Device fabrication & transport measurements on topological insulator nanostructure Ag2Te. - Lin, Qinghua. (2013)
Topological insulator, the new class of material with conducting surface and insulating bulk, is attracting much attention in research field. Theoretical calculations have predicted some material as topological insulators, and some of them have been verified experimentally. Experimental confirmation of topological insulators includes direct observation of the “Dirac cone” in electronic band structure via angle-resolved photoemission spectroscopy (ARPES), and also indirect transport studies to verify the presence of the conducting surface states. Recently, a theoretical study predicted that Ag2Te is a topological insulator. In this paper, we present a detailed description of material growth, device fabrication and four-terminal transport measurements on single crystal Ag2Te nanomaterial. We have observed Aharanov-Bohm (A-B) oscillation from magnetoresistance (MR) of Ag2Te nanowire. Together with temperature dependent MR of nanomaterial with different surface-to-volume ratio, we confirmed the presence of conducting surface states in Ag2Te. Also, angle dependent MR of nanoplate further supports this claim. The presence of conducting surface states, together with reported theoretical predictions, suggests that the conducting surface states are of topological nature, and that Ag2Te is a topological insulator. Presence of exotic phenomenon of linear, non-saturating MR, observed in other known topological insulator nanoribbon, further suggests that Ag2Te is a topological insulator.